Simple and Unbiased OSA Prescreening: Introduction of a New Morphologic OSA Prediction Score - Laharnar N (Dove Medical Press, 2021)
Naima Laharnar,1,* Sebastian Herberger,1,* Lisa-Kristin Prochnow,1 Ning-Hung Chen,2 Peter A Cistulli,3,4 Allan I Pack,5 Richard Schwab,5 Brendan T Keenan,5 Diego R Mazzotti,5,6 Ingo Fietze,1,7 Thomas Penzel1,8 1Department of Internal Medicine and Dermatology, Interdisciplinary Center of Sleep Medicine, Charité – Universitätsmedizin Berlin, Berlin, Germany; 2Department of Pulmonary and Critical Care Medicine, Sleep Center, Chang Gung Memorial Hospital, Taipei, Taiwan; 3Charles Perkins Centre, University of Sydney, Sydney, NSW, Australia; 4Department of Respiratory Medicine, Royal North Shore Hospital, Sydney, NSW, Australia; 5Department of Medicine/Division of Sleep Medicine, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, USA; 6Department of Internal Medicine, Division of Medical Informatics, University of Kansas Medical Center, Kansas City, KS, USA; 7The Federal State Autonomous Educational Institution of Higher Education I.M. Sechenov, First Moscow State Medical University of the Ministry of Health of the Russian Federation, Moscow, Russia; 8Department of Biology, Saratov State University, Saratov, Russia*These authors contributed equally to this workCorrespondence: Naima LaharnarDepartment of Internal Medicine and Dermatology, Interdisciplinary Center of Sleep Medicine, Charité – Universitätsmedizin Berlin, Campus Charité Mitte, Chariteplatz 1, Berlin, 10117, GermanyTel +49-30 450 513 120Email naima.laharnar@charite.dePurpose: An early prescreening in suspected obstructive sleep apnea (OSA) patients is desirable to expedite diagnosis and treatment. However, the accuracy and applicability of current prescreening tools is insufficient. We developed and tested an unbiased scoring system based solely on objective variables, which focuses on the diagnosis of severe OSA and exclusion of OSA.Patients and Methods: The OSA prediction score was developed (n = 150) and validated (n = 50) within German sleep center patients that were recruited as part of the Sleep Apnea Global Interdisciplinary Consortium (SAGIC). Six objective variables that were easy to assess and highly correlated with the apnea–hypopnea index were chosen for the score, including some known OSA risk factors: body-mass index, neck circumference, waist circumference, tongue position, male gender, and age (for women only). To test the predictive ability of the score and identify score thresholds, the receiver-operating characteristics (ROC) and curve were calculated.Results: A score ≥ 8 for predicting severe OSA resulted in an area under the ROC curve (ROC-AUC) of 90% (95% confidence interval: 84%, 95%), test accuracy of 82% (75%, 88%), sensitivity of 82% (65%, 93%), specificity of 82% (74%, 88%), and positive likelihood ratio of 4.55 (3.00, 6.90). A score ≤ 5 for predicting the absence of OSA resulted in a ROC-AUC of 89% (83%, 94%), test accuracy of 80% (73%, 86%), sensitivity of 72% (55%, 85%), specificity of 83% (75%, 89%), and positive likelihood ratio of 4.20 (2.66, 6.61). Performance characteristics were comparable in the small validation sample.Conclusion: We introduced a novel prescreening tool combining easily obtainable objective measures with predictive power and high general applicability. The proposed tool successfully predicted severe OSA (important due to its high risk of cardiovascular disease) and the exclusion of OSA (rarely a feature of previous screening instruments, but important for better differential diagnosis and treatment).Keywords: obstructive sleep apnea, diagnostic, sensitivity, specificity, screening